2022
DOI: 10.1039/d2bm00316c
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid linked β-glucan nanoparticles for liver specific oral delivery of biologics

Abstract: Oral delivery remains one of the most convenient routes for drug administration compared to intravenous, intramuscular, and via suppositories. However, due to the risk of degradation, and proteolysis of molecules...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Furthermore, YS can be constructed by conjugating β-glucans with other molecules to improve delivery, as performed by Chowdhury et al [ 49 ]. They synthesized a vehicle composed of taurocholic acid and β-glucan, capable of protecting molecules from the harmful environment of the stomach and accelerating the absorption of particles by the circulatory system, in addition to having target specificity for the liver, the organ of interest in the study.…”
Section: Characterization and Properties Of Yeast Shellsmentioning
confidence: 99%
“…Furthermore, YS can be constructed by conjugating β-glucans with other molecules to improve delivery, as performed by Chowdhury et al [ 49 ]. They synthesized a vehicle composed of taurocholic acid and β-glucan, capable of protecting molecules from the harmful environment of the stomach and accelerating the absorption of particles by the circulatory system, in addition to having target specificity for the liver, the organ of interest in the study.…”
Section: Characterization and Properties Of Yeast Shellsmentioning
confidence: 99%
“…Over the years, to overcome the limitations of the oral delivery of therapeutics, different approaches have been taken, and among them, a targeting-based drug delivery approach shows better effects. "It promotes the slow release of drug in the stomach, which subsequently extends the time available for drug dissolution and absorption in the stomach and/or small intestine [7,32,33]". However, there is still a lack of development of optimized formulations/vehicles that can be specifically delivered to the region of interest within the GI tract and exert their therapeutic effects for a longer duration [32].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that BG is very stable in acidic buffer, has a strong binding affinity with mucin, and forms microstructure particles in the presence of fatty acids . Studies show that the BG-based vehicle is highly effective in oral vaccine and protein delivery. , The BG-mediated mucoadhesive particle has the ability to protect therapeutic regimens from the harsh gastric environment, enhance retention of the therapeutic payload within the stomach for a longer duration, and maintain a sufficient therapeutic concentration for a prolonged period (6 h or more) . In addition, BG was found to act as an immune modulator of the gastrointestinal (GI) tract .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The BGmediated mucoadhesive particle has the ability to protect therapeutic regimens from the harsh gastric environment, enhance retention of the therapeutic payload within the stomach for a longer duration, and maintain a sufficient therapeutic concentration for a prolonged period (6 h or more). 17 In addition, BG was found to act as an immune modulator of the gastrointestinal (GI) tract. 18 Finally, BG has also shown significant potential in GI site-specific drug delivery to treat liver diseases, bowel disease, and stomach cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation